Nilai-Nilai Pendidikan Agama Islam Multikultural Dalam Turats Sirojuttholibin Kyai Ihsan Jampes Kediri - Al Anshori, Thoriq (AL MURABBI, 2024)
Multicultural differences are inevitable, especially in the academic life of primary and higher education. To accept this difference, one must be plural or tolerant of diversity. In the context of soul education, the great name Kyai Ihsan Jampes is no stranger to the general public. The purpose of this research is to find the values of multicultural Islamic education in the world's scholars of his origins to the extent to which, along with its analysis, as well as carefully studying the methods, approaches, and dimensions of multiculturalism existing in his turats. Methods used This research belongs to the category of library research and uses a qualitative descriptive approach. The values of multicultural Islamic education reflected by his Turats, at least, are the need to treat others with care, tolerance, and compassion, which is not at all compelling in calling for good. The methods reflected in the above turats are methods of contribution, decision-making, and social action. The approach is aesthetic. The dimensions contained are the dimensions of prejudice reduction.